(untitled) (Communications in Inorganic Synthesis, 2015)
Two new bis(triorganotin) 2-butynedioates, R3SnOOCC°CCOOSnR3 (where R = c-C6H11, 1; CH2C(CH3)2C6H5, 2), have been synthesized and characterized by means of elemental analysis, IR, and NMR (1H, 13C and 119Sn) spectra. The crystal structure of complex 2 is determined by X-ray single crystal diffraction. In the complexes, the carboxylate is monodentate and tin atom is four-coordinate in solid and non-coordinating solvent. Complex 2 is a centrosymmetric di-nuclear tin complex in which tin atom adopts a distorted tetrahedral geometry. Bioassay results have shown that the complexes have good in vitroantibacterial activity against Escherichia coli.